2021
DOI: 10.3390/biom11111588
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Proteins HSPA1 and HSP90AA1 Are Upregulated in Colorectal Polyps and Can Be Targeted in Cancer Cells by Anti-Inflammatory Oxicams with Arylpiperazine Pharmacophore and Benzoyl Moiety Substitutions at Thiazine Ring

Abstract: Heat shock proteins HSPA1/Hsp70α and HSP90AA1/Hsp90α are crucial for cancer growth but their expression pattern in colorectal polyps or whether they can be modulated by oxicams is unknown. We quantified (RTqPCR) HSPA1 and HSP90AA1 expression in 50 polyp-normal pairs in relation to polyp malignancy potential and examined the effect of piroxicam, meloxicam and five novel analogues on HSPA1 and HSP90AA1 expression (mRNA/protein) in colorectal adenocarcinoma lines. HSPA1 and HSP90AA1 were upregulated in polyps by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…They downregulate redox-sensitive and inflammation-associated transcription-factors NF-κB and AP-1, and reduce their DNA-binding capacity [ 21 ]. The NSAIDs have also been demonstrated to downregulate the expression of heat shock proteins [ 22 ], known regulators of cellular-redox status [ 23 ] and chemokine chaperones ( Figure 1 ). The oxicam protagonist, piroxicam, reduces the incidence and the size of tumors in animal models of CRC [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…They downregulate redox-sensitive and inflammation-associated transcription-factors NF-κB and AP-1, and reduce their DNA-binding capacity [ 21 ]. The NSAIDs have also been demonstrated to downregulate the expression of heat shock proteins [ 22 ], known regulators of cellular-redox status [ 23 ] and chemokine chaperones ( Figure 1 ). The oxicam protagonist, piroxicam, reduces the incidence and the size of tumors in animal models of CRC [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…BMMC cultured on CNC/agarose upregulated 7 genes that were effectively absent in cells that were cultured on agarose alone. These genes include heat shock proteins Hspa1a and Hspa1b which serve as chaperones for other proteins involved in cytoskeleton function and have been associated with atrial fibrillation and colorectal polyp formation ( Szczuka et al, 2021 ; van Marion et al, 2021 ). These proteins appear to be essential in cellular responses to changes in microenvironment and therefore it is unsurprising that their expression is induced in BMMC cultured on CNC/agarose.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that 25% of patients with neuroblastoma showed an MYCN amplification and predicted poor prognosis independently of other factors ( Brodeur et al, 1984 ; Seeger et al, 1985 ). HSP90AA1 , one of the HSP90 isoforms, showed a significant correlation with survival time in lung cancer patients by inhibiting the AKT1 and ERK pathways ( Niu et al, 2021 ) and was upregulated in colorectal cancer ( Szczuka et al, 2021 ). HSP90 regulates the stability of MLKL and RIP3 and is required for TNF-stimulated necrosome assembly ( Zhao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%